Effects of a multimedia campaign to increase human papillomavirus vaccine acceptance in Dhaka, Bangladesh - Sohail Agha; Sarah Francis; Drew Bernard; Aslam Fareed; Kasrina Azad; Firdausi Qadri (Human Vaccines & Immunotherapeutics)
Increasing the uptake of Human Papillomavirus (HPV) vaccine among adolescent girls is a high priority for the government of Bangladesh. This study examines correlates of HPV vaccine adoption in Dhaka Division, the largest division in Bangladesh. The 18-day vaccination campaign was accompanied by multimedia messages. We use the Fogg Behavior Model (FBM) as the theoretical framework for our analysis. Using a survey instrument based on the FBM, we analyze cross-sectional data collected from 611 caregivers of girls aged 9–17 in Dhaka. Survey data was collected in November and December 2023. Caregivers were recruited via Facebook and Instagram ads and interviewed through the Facebook Messenger App. About one-third of caregivers reported that their child had been vaccinated. We conducted bivariate and multivariate analyses to assess the relationships between the caregivers’ motivation, ability, exposure to the campaign and their child’s vaccination status. Adjusted odds ratios from logistic regression analyses, suggest that caregivers’ motivation, ability, and exposure to the multimedia campaign contributed to vaccine uptake. Caregivers’ motivation to get their child vaccinated was high (74%) but their ability was low (20%). Exposure to campaign messages had a dose-response relationship with vaccine adoption. However, 48% of caregivers remained unexposed to the multimedia campaign. We discuss challenges that the government’s HPV vaccination program is likely to face and identify program-related research questions that are important to answer for the success of future vaccination efforts.